Effects of NH4+/citrate complexing agent ratio on Ni–Mo and Ni–Mo–O electrodeposits from ammonium citrate baths - To, Dung T.; Park, Sun Hwa; Kim, Min Joong; Cho, Hyun-Seok; Myung, Nosang V. (Frontiers in Chemistry, 2022)
To understand the effect of complexing agents (i.e., ammonium and citrate) in nickel–molybdenum electrodeposition, calculation of the concentration of various Ni and Mo species as a function of pH and initial concentration of metal ions and complexing agents was performed. In addition, linear sweep voltammetry and Hull cell experiments were systematically investigated to understand the effect of current density and ammonium-to-citrate ratio to film compositions, morphology, and crystallinity. The results indicated that Ni(NH3)32+ played a critical role in induced co-deposition mechanism of Ni–Mo alloys, which involved the reduced Ni and absorbed H atoms. Microstructure analysis of deposits indicated that the transition from smooth laminarly grown amorphous Ni–Mo–O composites to columnar and nanocrystalline metallic Ni–Mo alloys with a globular structure as the ammonium-to-citrate molar ratio increases. The highest Mo content of alloys was as high as 19 at%, and up to 70 at% O was present in the composites.